The special expanded wrestling competition format: a conceptual proposal for wrestling competitions - Hafezikhah, A. (International Journal of Wrestling Science, 2025)
Traditional wrestling competitions are structured around individual matchups, limiting talent exposure, strategic depth, and team engagement. This paper introduces the SPECIAL EXPANDED WRESTLING COMPETITION FORMAT—a conceptual model in which each country fields a three-wrestler team per weight class. Matches are held as best-of-three series, with tactical elements such as lineup declarations, strategic substitutions, and the Golden Fall mechanism that can trigger a fourth deciding match under specific conditions. The SPECIAL EXPANDED WRESTLING COMPETITION FORMAT addresses key limitations of the current system by enabling broader athlete participation, enhancing the coach`s strategic role, and increasing psychological fairness through distributed responsibility. It also promotes media engagement and audience retention through multi-layered match narratives. The model is applicable to various competition levels, from national leagues to potential implementation in global formats such as a Wrestling Nations Cup. This article outlines the structure, logic, advantages, and possible criticisms of the SPECIAL EXPANDED WRESTLING COMPETITION FORMAT, offering a roadmap for pilot implementation and broader adoption. The paper concludes by positioning the SPECIAL EXPANDED WRESTLING COMPETITION FORMAT as a modernization strategy for wrestling—an evolution aligned with global trends in sports governance and audience engagement.